Research Progress on the Application and Migration Characteristics of Plant Essential Oils in Antibacterial Active Packaging：A Review - Jiaxin LI; Qiancheng ZHAO; Guanliang SONG; Xinrui SU; Shengcong LIU; Yongsheng MA (Shipin gongye ke-ji)
Plant essential oils are volatile, lipophilic compounds extracted from aromatic plants, most of which possess potent antibacterial properties, and some also have antioxidant effects. Combining plant essential oils with active packaging materials to prepare antimicrobial packaging can realize the controlled delivery of essential oils to packaged food and enhance the performance of the packaging system, so as to achieve the purpose of maintaining the sensory quality of food and prolonging the shelf life of food. This paper reviews the construction of antibacterial film, antibacterial sachets and antibacterial absorbent pads containing plant essential oil, and summarizes their application effects in the preservation of livestock meat, aquatic products and flour products. Essential oils in antibacterial packaging migrate to packaged food through diffusion, and the migration rate and amount are affected by the type and composition of essential oils, packaging materials, packaging environment relative humidity and temperature and other factors. Antibacterial packaging containing plant essential oils can realize active quality preservation of packaged food, and has a wide application prospect in food storage and circulation.